Meningkatkan Kinerja Berkelanjutan UMKM Melalui Manajemen Rantai Pasokan Halal - Jannah, Syayyidah Maftuhatul; Wijayanti, Dwi Marlina (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2025)
The purpose of this study is to examines the impact of implementing ten aspects related to halal supply chain management on its effectiveness, particularly in improving sustainability across economic, social, and environmental dimensions for MSMEs. The research adopts a quantitative research approach, collecting data through a self-administered survey conducted among MSMEs located in Yogyakarta, Indonesia. The results of the data analysis using SEM-PLS. The results indicate that six aspects of halal supply chain management significantly contribute to upholding halal integrity, enhancing customer satisfaction and branding, and improving process quality. Additionally, a higher implementation of these aspects is directly linked to an enhancement in the sustainable performance of MSMEs. This research provides insight that MSMEs still need to be fostered in implementing Halal Supply Chain Management.